2023
DOI: 10.1177/10105395231212024
|View full text |Cite
|
Sign up to set email alerts
|

General Self-Efficacy in Association With Insomnia Symptoms and Suicidal Ideation Among Chinese Community-Based Population

Ying Li,
Guangming Xu,
Di Wu
et al.

Abstract: Previous studies supported the association between insomnia symptoms and suicidal ideation in patients with mental or psychological diseases. This study aimed to examine the associations between insomnia symptoms, general self-efficacy, and suicidal ideation among community-based adult population. Standardized questionnaire was distributed to 2051 community-dwelling adults in Lishui district of Jiangsu Province in China, to assess their socio-demographics, insomnia symptoms, general self-efficacy, and suicidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…In the analysis of the effect of self-efficacy, we found that it behaves as a clear protector against insomnia and in a sustained manner over time, buffering the effects of being in stressful work situations. Recent research has found an association between self-efficacy and insomnia in the general population, in line with our results [ 60 , 61 ]. Meanwhile, specifically among nurses it has been found that in stressful work situations, self-efficacy acts as a clear protector in the management of anxiety and can even have positive consequences, such as the development of a resilient personality, if the anxiety derived from stressful work situations is managed through self-efficacy [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the analysis of the effect of self-efficacy, we found that it behaves as a clear protector against insomnia and in a sustained manner over time, buffering the effects of being in stressful work situations. Recent research has found an association between self-efficacy and insomnia in the general population, in line with our results [ 60 , 61 ]. Meanwhile, specifically among nurses it has been found that in stressful work situations, self-efficacy acts as a clear protector in the management of anxiety and can even have positive consequences, such as the development of a resilient personality, if the anxiety derived from stressful work situations is managed through self-efficacy [ 62 ].…”
Section: Discussionsupporting
confidence: 93%